2019
DOI: 10.3390/molecules24030383
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Immobilized Titanium Dioxide Nanostructures by Argon Plasma for Photocatalytic Removal of Organic Dyes

Abstract: The aim of this study was to modify surface properties of immobilized rutile TiO2 using Argon cold plasma treatment and to evaluate the performance of the catalyst in photocatalytic elimination of synthetic dyes in UV/TiO2/H2O2 process. The surface-modified TiO2 was characterized by XRD, EDX, SEM, UV-DRS and XPS analyses. Response surface methodology was adopted to achieve high catalyst efficiency by evaluating the effect of two main independent cold plasma treatment parameters (exposure time and pressure) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Furthermore, as established in this study, the photon lifetime could be elongated on the PhC surface, and the optical absorption could be enhanced because the PhCs had unique optical characteristics that allowed them to manipulate and confine the light incident on their surface [34]. In addition, the nanostructured materials such as PhC supported photocatalysts were reported to show an increase in their photocatalytic degradation efficiency [17,35]. Therefore, it was shown that the 2D-PhC underneath the TiO 2 coating played a synergistic role in enhancing the rate of UV mediated photocatalytic degradation of CR and AB-10 significantly after the timepoints of 60 and 80 min.…”
Section: Photocatalytic Degradation Of Cr and Ab-10bmentioning
confidence: 58%
See 1 more Smart Citation
“…Furthermore, as established in this study, the photon lifetime could be elongated on the PhC surface, and the optical absorption could be enhanced because the PhCs had unique optical characteristics that allowed them to manipulate and confine the light incident on their surface [34]. In addition, the nanostructured materials such as PhC supported photocatalysts were reported to show an increase in their photocatalytic degradation efficiency [17,35]. Therefore, it was shown that the 2D-PhC underneath the TiO 2 coating played a synergistic role in enhancing the rate of UV mediated photocatalytic degradation of CR and AB-10 significantly after the timepoints of 60 and 80 min.…”
Section: Photocatalytic Degradation Of Cr and Ab-10bmentioning
confidence: 58%
“…The absorbance values at~494 for CR and~630 nm for AB-10B (λ max) were measured before and after UV irradiation. The degradation rate (η) of the respective dyes on TiO 2 coated 2D-PhC was calculated by Equation (1) [17]:…”
Section: Photocatalytic Degradation Of Cr and Ab-10bmentioning
confidence: 99%
“…The distribution of residual among the performed experiments is demonstrated in Figure 4. Random distribution of residuals, observed in this figure, signals the reliability of proposed models [36]. Figure 5 presents the normal probability plot of residuals of simultaneous RB and AR14 degradation process.…”
Section: Rsm Modelingmentioning
confidence: 67%
“…In summary, this research performed an investigation of different parameters on membrane fabrication and various parameters on the fabrication of a nanocomposite PES/TiO 2 membrane. Fabrication variables, including exposure time [31], immersion time [32], the solvent ratio (ratio of less volatile solvent (NMP) to more volatile solvent DMAc), glycerol time (pore filling time), and the nonsolvent ratio (isopropanol to water) were set individually. According to the analysis of the two-level factorial design, glycerol time, solvent ratio, and nonsolvent ratio were the most important factors which should be set accurately.…”
Section: Resultsmentioning
confidence: 99%